Multi-location evaluation of gene pyramided lines of MTU 1010 and JGL 1798 against bacterial blight of rice - G. UMA DEVI, A. YUGANDER, C. SRINIVAS, R.M. SUNDARAM; G.S. LAHA*, G. PADMAJA, CH. V. DURGA RANI (Indian Phytopathology, 2017)
Cottondora Sannalu (MTU 1010) and Jagitial Sannalu (JGL 1798) are widely cultivated rice varieties in Telangana and Andhra Pradesh and very popular among the farmers because of their high yield, slender grain and good cooking quality. Despite their popularity, they are susceptible to many pests and diseases including bacterial blight (BB), caused by Xanthomonas oryzae pv. oryae (Xoo). Two BB resistance genes viz., xa13 and Xa21 were introgressed in these two varieties using marker assisted backcross breeding. Homozygous lines possessing BB resistance genes xa13 or Xa21 and their combination were evaluated for BB resistance with multiple Xoo isolates under controlled condition in glass house and also at different hot spot locations in the states of Telangana and Andhra Pradesh, India. Both the recurrent parents (MTU 1010 and JGL 1798), TN1 (susceptible check) and Improved Samba Mahsuri (resistant check) were also included for resistance evaluation. All the gene-pyramided lines showed high level of resistance against BB both under glass house and field condition. Individually, BB resistance gene xa13 showed higher level of resistance than Xa21. The level of resistance was higher in the lines possessing both the BB resistance genes compared to the lines possessing single BB resistance genes. The results showed that combination of BB resistance genes xa13 and Xa21 can provide broad level of resistance against BB in Telangana and Andhra Pradesh.